Inclusive Learning Strategies for Children with Special Needs at PAUD Level: Transformative or Sustainable Education - Isnaini Budi Hastuti; Rusdiani Nurtina Irsad (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2025)
The concept of early childhood learning continues to develop in line with the demands of the times, where education is faced with two equally important approaches, namely, transformative education and sustainable education. This paper aims to delve deeper into transformative and sustainable education concepts in applying inclusive learning for children with special needs at the ECE level. Data were collected through participatory observation in three inclusive ECEs at [research site], in-depth interviews with 15 teachers and parents, and analysis of curriculum documents. Data validation is carried out through triangulation of sources and techniques, while data analysis refers to the Miles-Huberman interactive model, which includes data reduction, data presentation, and conclusion verification. The study results show that inclusive learning for children with special needs at the early childhood education level should not be trapped in the dichotomy between transformative and sustainable education. On the contrary, integrating the two approaches is an ideal solution based on the principles of early childhood learning, so that it can develop the moral and intellectual transformation of individuals oriented towards sustainability. In other words, early childhood learning must function as a means of change (transformation) based on sustainability values to create a society that aligns with education's goals. Inclusive learning practices based on transformative education and sustainable education in ECE open up great opportunities to create meaningful education for all children, including children with special needs. This approach benefits the child's individual development and shapes an inclusive and sustainable school culture.